2013
DOI: 10.1021/es402962j
|View full text |Cite
|
Sign up to set email alerts
|

Surface Complexation and Oxidation of SnII by Nanomagnetite

Abstract: The long-lived fission product 126Sn is of substantial interest in the context of nuclear waste disposal in deep underground repositories. However, the prevalent redox state, the aqueous speciation as well as the reactions at the mineral-water interface under the expected anoxic and reducing conditions are a matter of debate. We therefore investigated the reaction of Sn(II) with a relevant redox-reactive mineral, magnetite (Fe(II)Fe(III)2O4) at <2 ppmv O2, and monitored Sn uptake as a function of pH and time. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…34 In the Sn K-edge XANES spectra of Figure 1e, the oxidation state of tin in the Fe 2.76 Sn 0.24 O 4 /rGO and Fe 2.64 Sn 0.36 O 4 /rGO composites possesses a similar oxidation state of Sn 4+ . 23 The peaks between 0.5 and 2 Å and 2 and 4 Å of all the composites in Figure 1f the typical feature of SnO 2 , in the Fe 2.76 Sn 0.24 O 4 /rGO and Fe 2.64 Sn 0.36 O 4 /rGO composites, the tin is coordinated by six oxygen atoms at the first coordination shell, 39,40 which indicates that the tin atoms in the Fe 3−x Sn x O 4 composite adopt the octahedral site in the inverse cubic spinel structure and also demonstrates that the substitution of Fe 3+ by Sn 4+ is achieved at the octahedral site. 39,40 Considering the occupancy of the octahedral and tetrahedral site (as noted above, all of the Fe 2+ and half of Fe 3+ , and the remaining Fe 3+ is located at the octahedral and tetrahedral site, respectively) and the size of the ionic radius (as noted above, 0.78 and 0.65 Å for Fe 2+ and of Fe 3+ , respectively), the octahedral site is more voluminous than the tetrahedral site, and, as a consequence, it is occupied by the Sn 4+ .…”
Section: Resultsmentioning
confidence: 90%
“…34 In the Sn K-edge XANES spectra of Figure 1e, the oxidation state of tin in the Fe 2.76 Sn 0.24 O 4 /rGO and Fe 2.64 Sn 0.36 O 4 /rGO composites possesses a similar oxidation state of Sn 4+ . 23 The peaks between 0.5 and 2 Å and 2 and 4 Å of all the composites in Figure 1f the typical feature of SnO 2 , in the Fe 2.76 Sn 0.24 O 4 /rGO and Fe 2.64 Sn 0.36 O 4 /rGO composites, the tin is coordinated by six oxygen atoms at the first coordination shell, 39,40 which indicates that the tin atoms in the Fe 3−x Sn x O 4 composite adopt the octahedral site in the inverse cubic spinel structure and also demonstrates that the substitution of Fe 3+ by Sn 4+ is achieved at the octahedral site. 39,40 Considering the occupancy of the octahedral and tetrahedral site (as noted above, all of the Fe 2+ and half of Fe 3+ , and the remaining Fe 3+ is located at the octahedral and tetrahedral site, respectively) and the size of the ionic radius (as noted above, 0.78 and 0.65 Å for Fe 2+ and of Fe 3+ , respectively), the octahedral site is more voluminous than the tetrahedral site, and, as a consequence, it is occupied by the Sn 4+ .…”
Section: Resultsmentioning
confidence: 90%
“…The release of Fe­(II) from hydrogen-driven steel corrosion and subsequent precipitation of magnetite may create a highly dynamic system where one could envision that Pu is incorporated by magnetite following either a coprecipitation process or by overgrowth of an already existing magnetite surface with adsorbed Pu. Such a process has been observed, for instance, for Tc­(IV) and Sn­(IV), two cations with ionic radii (0.65 and 0.69 Å, respectively) similar to those of Fe­(II) or Fe­(III) (0.78 and 0.65 Å, respectively), which therefore can easily replace Fe in octahedral sites. ,, More surprisingly, from a crystal-chemical point of view, this has also been demonstrated for the larger actinide U. In this case, U is preferentially incorporated in its pentavalent oxidation state, by adopting an uranate-type local structure characterized by relaxation of the multiply bonded “-yl” oxygen ligands.…”
Section: Introductionmentioning
confidence: 79%
“…Such a process has been observed, for instance, for Tc(IV) and Sn(IV), two cations with ionic radii (0.65 and 0.69 Å, respectively) similar to those of Fe(II) or Fe(III) (0.78 and 0.65 Å, respectively), which therefore can easily replace Fe in octahedral sites. 32,37,38 More surprisingly, from a crystal-chemical point of view, this has also been demonstrated for the larger actinide U. 39−41 In this case, U is preferentially incorporated in its pentavalent oxidation state, by adopting an uranate-type local structure characterized by relaxation of the multiply bonded "-yl" oxygen ligands.…”
Section: ■ Introductionmentioning
confidence: 85%
“…When looking for the elemental distribution of Sn with TEM, one finds that Sn is predominately associated with goethite and only to a smaller part with the newly formed magnetite nanoparticles. This suggests that Sn remains bound to goethite after oxidation, in line with the EXAFS spectra, which show neither the structure of the tetradentate sorption complex at the surface of magnetite nor Sn IV structurally incorporated by magnetite (Figures and ) . Therefore, there is no substantial re-distribution of sorbed Sn from goethite to magnetite within the given reaction time.…”
Section: Resultsmentioning
confidence: 52%
“…Previous studies have shown that Fe minerals with a low band gap such as magnetite efficiently catalyze redox reactions at their surface . This has been confirmed for Sn II , which is rapidly oxidized at the surface of magnetite particles to Sn IV , which forms a tetradentate inner-sphere sorption complex . The formation of this complex can be adequately predicted with a double-layer surface complexation model.…”
Section: Introductionmentioning
confidence: 67%